Novel impact absorption materials for sport application - Tan, Kevin Bo Lin (Nanyang Technological University, 2021)
The high number of injuries caused by sports activities had increase the demand for better impact-protective clothing and equipment. This had brought the need to explore various materials that has the capability to minimize the injuries. Polyborosiloxane (PBS) is silicone-based polymer that exhibit the viscoelastic properties which could be used as impact absorption materials for sport application. In this project, a series of PBS was synthesized using different number average molecular weight of hydroxy-terminated polydimethylsiloxanes (PDMS) and boric acid (BA) in toluene at 140 °C. To identify the type of bonding in PBS, the Fourier transform infrared (FTIR) spectroscopy was conducted. The formation Si−O−B bonds and B: O − Si weak bonding identified in PBS create the boron linkage. The influence of molecular weight of PDMS on viscoelastic behaviour of the PBSs was investigated by dynamic rheometer. The result has shown that a storage and loss modulus is largely dependent on molecular weight of PDMS which control the amount of boron linkage formed. It was concluded that PBS synthesized by low molecular weight of PDMS creates more boron linkage and thus exhibit a better viscoelastic property.